1997
DOI: 10.1128/iai.65.10.4082-4089.1997
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion to and invasion of HeLa cells by pathogenic Escherichia coli carrying the afa-3 gene cluster are mediated by the AfaE and AfaD proteins, respectively

Abstract: The afa-3 gene cluster, expressed by uropathogenic and diarrhea-associated Escherichia coli strains, determines the formation of an afimbrial adhesive sheath composed of the AfaD and AfaE-III adhesins. The adherence to HeLa cells by recombinant HB101 strains producing both or only one of these two adhesins was investigated. Ultrastructural analyses of the interaction and gentamicin protection assays showed adherence to HeLa cells by HB101 producing both the AfaD and AfaE-III proteins and internalization of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 30 publications
2
101
0
Order By: Relevance
“…Data coming from studies using drugs inhibiting endocytosis and microscopy studies also suggest a possible role of clathrin-dependent endocytosis in the entry of E. coli [38][39][40][41], Staphylococcus aureus [42,43], Streptococcus pneumoniae [44,45], Streptococcus dysgalactiae [46], Ehrlichia risticii [17,47], Brucella abortus [48], Klebsiella pneumoniae [49], Legionella pneumophila [50], Campylobacter jejuni [51] and Citrobacter freundii [51]. More controversial is the role of clathrin-dependent endocytosis in Neisseria and Chlamydia invasion.…”
Section: Other Bacteriamentioning
confidence: 99%
“…Data coming from studies using drugs inhibiting endocytosis and microscopy studies also suggest a possible role of clathrin-dependent endocytosis in the entry of E. coli [38][39][40][41], Staphylococcus aureus [42,43], Streptococcus pneumoniae [44,45], Streptococcus dysgalactiae [46], Ehrlichia risticii [17,47], Brucella abortus [48], Klebsiella pneumoniae [49], Legionella pneumophila [50], Campylobacter jejuni [51] and Citrobacter freundii [51]. More controversial is the role of clathrin-dependent endocytosis in Neisseria and Chlamydia invasion.…”
Section: Other Bacteriamentioning
confidence: 99%
“…Moreover, DA adhesion onto Hep-2 or HeLa cells has been also observed for UPEC strains expressing Afa-I (37), Afa-III (28), and Dr (38). Goluszko et al (39) have proposed a HeLa cell receptor assay designated the diffuse clustering assay (DCA), which associates the cell diffuse adhesion of Afa/Dr DAEC with the property of Afa/Dr adhesins to promote hDAF receptor clustering around adhering bacteria (40)(41)(42). However, the DCA did not detect all the E. coli strains bearing Afa/Dr adhesins, considering that AfaE-VII and AfaE-VIII adhesins did not recognize hDAF (26).…”
Section: Epidemiology Detectionmentioning
confidence: 99%
“…Nuclear magnetic resolution and biophysical studies have revealed that the structural organization of Afa-III adhesin develops by assembly onto the bacterial membrane usher of AfaE-III adhesins subunits (158,159) capped by the AfaD-III subunit (166)(167)(168). The AfaD-III subunit also has the ability to separate from the Dr fimbriae (42). A diffuse and not well-ordered cell surface localization of the AfaD-III subunit has been observed by immunoelectron microscopy (42,168,169).…”
Section: Afa/dr Adhesinsmentioning
confidence: 99%
See 2 more Smart Citations